E-Resources in Economics: A Case Study of e-ShodhSindu Consortium for Higher Education: Exploring e-Resource Availability in Economics: A Case Study (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Today Library and Information Centres are playing an important role in providing access to web based resources and services to its user community. The purpose for this paper is to investigate the availability of various kinds of e-resources like e-journals and electronic databases particularly in the field of Economics. E-resources are the necessity of the time and also have turned into the face estimation of any scholastic organization. This paper endeavours to recognize the types of e-journals and e-databases provided to member universities through eShodhSindhu Consortium for Higher Education